Sports - Oxlade, Chris; Cotugno, Megan; Dharmapala, Vaarunika; Mead, Steve; Throp, Claire (Chicago Raintree, 2012)
This book explores the science behind sports. It looks at topics such as healthy food and how the body works during sports. It also explores the concepts of streamlining and friction
A gift from book Africa
Sports
NEW_ZTN_GN
Keywords: Sports sciences; Health & fitness -- Aerobics